Corrosion behaviour of Fe-based austenitic and Ni-based alloys in Wet CO2 gas with and without chloride deposits at 650 °C. (January 2023) - Cai, Yuchen; Nguyen, Thuan Dinh; Zhang, Jianqiang; Gleeson, Brian; Young, David J.
Abstract: The corrosion behaviour of Fe-25Cr-20Ni, 310SS, Ni-25Cr, and Ni-25Cr-2Mn-1Si (all in wt%) with and without NaCl-KCl deposits in Ar-60%CO2 -20%H2 O gas at 650 °C was investigated. Without salt deposits, both Fe-25Cr-20Ni and Ni-25Cr formed thick internal oxidation zones (IOZs) and external oxide scales. The addition of Si+Mn significantly improved the corrosion resistance in this case. The presence of NaCl-KCl deposits accelerated the corrosion, forming porous external oxide scales and IOZs, with no protective effect provided by Si+Mn alloying. The effect of chlorides was discussed in terms of oxide volatilization and the accelerated reaction of chlorine with oxides in the IOZs. Highlights: Fe-25Cr-20Ni and Ni-25Cr alloys experienced breakaway oxidation in wet CO2 gas with and without chlorides. The protective effect of the additional Si and Mn disappeared in the presence of chlorides. The presence of chlorides accelerated corrosion by forming porous products via volatilization reactions. Internal arrays of pores formed according to the active oxidation effects on intragranular carbides.